(untitled) (The Journal of Plant Protection Sciences, 2021)
Som (Persea bombycina, King. ex Hook. f. Kost.), the primary food plant of muga silkworm, (Antheraea assamensis Helfer) growing mainly in North Eastern region and Uttaranchal State in India. India is unique in producing the golden muga silk and has monopoly in global silk market grows up to 20-25 meters and survives for 18-20 years. Pollarding of Som plant at 6 ft height is a common practice in North Eastern region of India for controlled rearing (outdoor) of muga silkworm. It was observed that stems of som plant (specifically the pollarded plants) were generally infected with rot disease when it grows older. Phellinus contigus (under Polyporaceae), a white rot fungus, causes heart rot disease and Biscogniauxia mediterranea (= Hypoxylon mediterranea) (under Xylariaceae) causes canker rot disease of Som plant. A survey was conducted to study the infection of rotting pathogens on Som plants at Regional Muga Research Station (RMRS), Boko, Assam, India with during 2004-06. The disease incidence (DI %) caused by B. mediterranea was 12% while P.contigus showed 20% infection. Corelating the age of Som plants with susceptibility rot infection was found to be maximum in 10 years old plantation.